Expressive Speech Acts in the Comments Section of One Direction’s Youtube Channel - Putra Danan Jaya; Putu Lirishati Soethama; Ida Ayu Made Puspani (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study examines expressive speech acts in the comments section of One Direction’s YouTube video titled “10 Years of One Direction.” It aims to identify the types of expressive acts used, explore their communicative purposes, and determine which type is most frequently employed. The research uses Searle and Vanderveken’s (1985) classification—which includes acts such as thanking, apologizing, congratulating, praising, sorrowing, boasting, blaming, and greeting—and Leech’s (2014) categorization of speech act functions (competitive, convivial, collaborative, and conflictive). Using a descriptive qualitative approach supported by basic quantitative analysis, the study analyzes 70 selected comments from the video. Results show eight types of expressive speech acts: thanking, congratulating, praising, sorrowing, blaming, happiness, boasting, and regretting. These acts mostly serve convivial, collaborative, and conflictive functions. Notably, sorrowing was the most frequent, appearing in 28.57% of the comments, indicating a strong nostalgic and emotional response among fans. The findings highlight how digital fan communities use expressive language to share emotions and build collective memories.